Gene copy number is associated with phytochemistry in Cannabis sativa. Issue 6 (20th November 2019) - Vergara, Daniela; Huscher, Ezra L; Keepers, Kyle G; Givens, Robert M; Cizek, Christian G; Torres, Anthony; Gaudino, Reggie; Kane, Nolan C
Abstract: Gene copy number (CN) variation is known to be important in nearly every species where it has been examined. Alterations in gene CN may provide a fast way of acquiring diversity, allowing rapid adaptation under strong selective pressures, and may also be a key component of standing genetic variation within species. Cannabis sativa plants produce a distinguishing set of secondary metabolites, the cannabinoids, many of which have medicinal utility. Two major cannabinoids—THCA (delta-9-tetrahydrocannabinolic acid) and CBDA (cannabidiolic acid)—are products of a three-step biochemical pathway. Using whole-genome shotgun sequence data for 69 Cannabis cultivars from diverse lineages within the species, we found that genes encoding the synthases in this pathway vary in CN. Transcriptome sequence data show that the cannabinoid paralogs are differentially expressed among lineages within the species. We also found that CN partially explains variation in cannabinoid content levels among Cannabis plants. Our results demonstrate that biosynthetic genes found at multiple points in the pathway could be useful for breeding purposes, and suggest that natural and artificial selection have shaped CN variation. Truncations in specific paralogs are associated with lack of production of particular cannabinoids, showing how phytochemical diversity can evolve through a complex combination of processes. Abstract : The cannabinoid compounds, with high medicinal promise, are a main characteristic of the plant Cannabis sativa . These compounds were thought to have a simple mode of inheritance; however, our work describes multiple gene copies involved in their production. We found that first, varieties and individuals differ in the number of gene copies. Second, the number of copies may be related to the amount of cannabinoid production. Third, the expression of these genes also varies within varieties. An interesting remaining unknown from this study is the multiple other genes with unknown products, which could also have medicinal importance.